Busy going nowhere [video cassette] - TV Choice Productions (London TV Choice Productions, 1992)
Summary: This dramatised case study offers a vivid insight into critical organisational problem and highlights the way in which companies are all to easily diverted from their real business aims
Colour recording system: PAL
Keywords: Management; Organization; Organizational effectiveness